Multimodal assessment of orbital immune cell infiltration and tissue remodeling during development of graves disease by 1H19F MRI. Issue 2 (27th January 2018) - Flögel, Ulrich; Schlüter, Anke; Jacoby, Christoph; Temme, Sebastian; Banga, J. Paul; Eckstein, Anja; Schrader, Jürgen; Berchner‐Pfannschmidt, Utta
Abstract : Purpose: To evaluate key molecular and cellular features of Graves orbitopathy (GO) by simultaneous monitoring of alterations in morphology, inflammatory patterns, and tissue remodeling. Methods: To this end, we utilized a murine model of GO induced by immunization with a human thyroid‐stimulating hormone receptor A‐subunit plasmid. Altogether, 52 mice were used: 27 GOs and 25 controls (Ctrl) immunized with β‐galactasidose plasmid. From these, 17 GO and 12 Ctrl mice were subjected to multimodal MRI at 9.4T, whereas 23 mice only underwent histology. Beyond anatomical hydrogen‐1 ( 1 H) MRI, we employed transverse relaxation time (T2 ) mapping for visualization of edema, chemical exchange saturation transfer (CEST) for detection of hyaluronan, and fluorine‐19 ( 19 F) MRI for tracking of in situ‐labeled immune cells after intravenous injection of perfluorcarbons (PFCs). Results: 1 H/ 19 F MRI demonstrated substantial infiltration of PFC‐loaded immune cells in peri and retro‐orbital regions of GO mice, whereas healthy Ctrls showed only minor 19 F signals. In parallel, T2 mapping indicated onset of edema in periorbital tissue and adjacent ocular glands ( P = 0.038/0.017), which were associated with enhanced orbital CEST signals in GO mice ( P = 0.031). Concomitantly, a moderate expansion of retrobulbar fat ( P = 0.029) was apparent; however, no signs for extraocular myopathy were detectable. 19 F MRI‐based visualization of orbital inflammation exhibited the highest significance level to discriminate between GO and Ctrl mice ( P = 0.006) and showed the best correlation with the clinical score ( P = 0.0007). Conclusion: The present approach permits the comprehensive characterization of orbital tissue and holds the potential for accurate GO diagnosis in the clinical setting. Magn Reson Med 80:711–718, 2018. © 2018 International Society for Magnetic Resonance in Medicine.